Pious ecological sophistry: A solution to the environmental crises or an addition to noise pollution? (Hekima Review, 2010)
Four decades after the celebration of the first Earth Day in 1970, public apprehension over the rate of environmental degradation and its telling effects on humanity has surged to unprecedented levels. Even though some sections of human society still consider environmental crises as myths, many people, including highly respected scientists, have joined the rising clamour for environmental protection. Pro-environmentalists who were once dismissed as ‘ecofreaks’ and ‘tree-huggers’1 are no longer labeled as such but continue to have many people support their cause. A number of reasons account for this increased environmental awareness. Some of these reasons emerge in different disguises and are all tailored to the strange environmental occurrences: energy scarcity, acid rain, build-up of toxic and hazardous wastes, ozone depletion, water shortages, massive soil erosion, global atmospheric, terrestrial and aquatic pollution, climate change, forest dieback and tropical deforestation, floods, droughts, earthquakes, typhoons, hurricanes, landslides, volcanoes, rapid extinction of plant and animal species, regional imbalances in numbers of people and food required to feed them. These problems continue to soar in spite of an increasing national and international environmental awareness and legislation. This article considers the global environmental crises and how politicizing these problems and non-viable environmental ethical theories depress rather than impress efforts to solve them. The article then suggests a “moderate anthropocentrism” as a viable ethic and makes an appeal for the de-politicization of environmental issues so as to create and sustain the political will necessary for positive action.